A Deep Learning System for Automated Weld Seam and Surface Defect Inspection - Neves, João A. G.; Oliveira, Davidson Nunes de; Maia, Helton (Anais da Escola Regional de Alto Desempenho da Região Nordeste (ERAD-NE), 2025)
This work presents a deep learning-based system for automated weld seam and surface defect inspection. A REST API with NestJS sends uploaded images to a secure FastAPI service running a YOLOv11 model, which returns predictions with class, confidence, and bounding boxes. The system delivers high accuracy, reduces human error, and supports deployment on various devices, including smartphones, for flexible industrial integration.